1986
DOI: 10.1007/bf02144130
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological findings in eyes after silicone oil injection

Abstract: Eight eyes were examined histologically after silicone oil injection. Intraretinal deposits suggestive of silicone were not present in attached retinas, but were frequently observed in detached retinas when subretinal silicone occurred. This may possibly be due to defects in the horizontal conducting structures of the retina such as those occurring in persistent detachment with disorganization of the retina. Morphologically, the retina was essentially normal 3.5 years after the silicone injection. This observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
1
2

Year Published

1986
1986
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 4 publications
3
28
1
2
Order By: Relevance
“…29 30 In the retinectomy oil specimens, intraretinal silicone oil was observed only when the retinal architecture was severely disorganised, suggesting that retinal injury is a prerequisite for oil infiltration. Kirchof et al, 31 in a case series of eight eyes, reported that intraretinal silicone oil was absent unless accompanied by subretinal oil. In addition, animal studies did not find silicone oil in the outer retinal layer unless injected subretinally, 32 and it has been postulated that this may be because of the integrity of the outer limiting membrane.…”
Section: Discussionmentioning
confidence: 98%
“…29 30 In the retinectomy oil specimens, intraretinal silicone oil was observed only when the retinal architecture was severely disorganised, suggesting that retinal injury is a prerequisite for oil infiltration. Kirchof et al, 31 in a case series of eight eyes, reported that intraretinal silicone oil was absent unless accompanied by subretinal oil. In addition, animal studies did not find silicone oil in the outer retinal layer unless injected subretinally, 32 and it has been postulated that this may be because of the integrity of the outer limiting membrane.…”
Section: Discussionmentioning
confidence: 98%
“…Bambas et al [14] found toxic low-molecular-weight components in SiO samples removed from eyes after several months. Several studies showed oil droplets in epiretinal membranes, retina, and optic nerve [32][33][34][35][36][37][38] . In our study, we could not find clear signs of retained SiO within retinal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Silicone oils also have other disadvantages, including increased postoperative cataract formation and glaucoma development and the need for surgical removal. [26][27][28][29][30][31] Additionally, silicone oil is hydrophobic, so it is not possible to completely fill the vitreous cavity with it. As a result, a fluidic space is created where growth factors can accumulate and proliferative membranes can form.…”
Section: Discussionmentioning
confidence: 99%